Relationship between Workload and Nurses' Performance in the Implementation of Hospital Health Services in Makassar - Rusli, Rusli; Sima, Yenny; Sembiring, Lisma Natalia Br; Nursinah, Andi; Zaenal, Zaenal; Mustamin, Rini (International Journal of Health Sciences, 2024)
Health care is any effort organized alone or together in an organization to maintain and improve the health of individuals, families, groups and or communities. Documentation in nursing is an important part of the action taken by nurses after performing nursing actions. The records carried out contain reports that are needed to decide on assessment, diagnosis, develop nursing plans, implement and evaluate nursing activities, which have been designed in a structured, valid and able to be accounted for both morally and legally. The purpose of the study was to determine the relationship between workload and nurse performance in the implementation of nursing care. This research is descriptive research. This research took place in the treatment room of Makasar City Hospital. The population in this study were all nurses who served in the treatment room of Makasar City Hospital and the research sample was 35 nurses using the Total Sampling Technique. Data analysis using Univariate and Bivariate analysis using statistical tests with a level of meaning α = 0.05. The statistical test used is Chi- square using the SPSS computer program version 25.0 for windows. The results of the study using the Chi-square statistical test using SPSS on the relationship between workload and the performance of the implementation of nursing care documentation in the treatment room of Makassar City Hospital obtained a p-value = 0.001 or smaller than a = 0.05, then H0 is rejected and Ha is accepted, which means that there is a relationship between workload and the implementation of nursing care documentation.